1971
DOI: 10.1111/j.1432-1033.1971.tb01515.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Study of the Dicarboxylate Carrier in Rat Liver Mitochondria

Abstract: The rate of uptake in mitochondria as catalyzed by the dicarboxylate carrier of dicarboxylates and, in the presence of N-ethylmaleimide, of inorganic phosphate, has been analyzed by using the inhibitor stop method.1. By comparing the dependence on substrate concentration of the rate of succinate, malonate and malate uptake, it is found that the K , (malate) = 0.23 < Km (malonate) = 0.37 < K m (succinate) = 1.17 mM. The V values, however, are not significantly different for all three dicarboxylates ( V = 70 pmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
83
0
1

Year Published

1972
1972
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(88 citation statements)
references
References 15 publications
4
83
0
1
Order By: Relevance
“…However, Fonyo and Ligeti investigated the role of Pi in cation uptake using mersalyl and NEM, and concluded that PiC was an important H + donor for respiration [38] (Figure 1). A small early onset burst remained in the presence of mersalyl, and this was found to be inhibited by butylmalonate, an inhibitor of the dicarboxylate carrier (DIC) which catalyzes the exchange of dicarboxylic acids (e.g., malate or succinate) for Pi [39]. It was concluded that both the PiC and the DIC have the possibility to support cation-stimulated respiration [40].…”
Section: Role Of the Pic In Oxidative Phosphorylationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Fonyo and Ligeti investigated the role of Pi in cation uptake using mersalyl and NEM, and concluded that PiC was an important H + donor for respiration [38] (Figure 1). A small early onset burst remained in the presence of mersalyl, and this was found to be inhibited by butylmalonate, an inhibitor of the dicarboxylate carrier (DIC) which catalyzes the exchange of dicarboxylic acids (e.g., malate or succinate) for Pi [39]. It was concluded that both the PiC and the DIC have the possibility to support cation-stimulated respiration [40].…”
Section: Role Of the Pic In Oxidative Phosphorylationmentioning
confidence: 99%
“…Pi uptake can also be mediated by the DIC and the ATP-Mg/Pi carriers [39,62] (Figure 1) but the primary pathway likely is provided by the PiC [40]; however, this evidence rests on potentially non-specific reagents such as NEM and mersalyl. Notably, PiC has also been proposed to undergo a Ca 2+ -induced cyclophilin D (CyPD)-mediated conformational change providing a mechanism central to the opening of the PTP [63].…”
Section: Role Of Pic In Calcium Handlingmentioning
confidence: 99%
“…When the chloride derivatives were not commercially available, they were made from oxalylchloride, or thionyle chloride and the corresponding fatty acids. Dicarboxylate transport was tested as uptake of [ 14C]malate [9] at O'C. The medium was made of 0.1 M KCl, 2.5 mM Tris-MES (pH 6.5) 1 mM EGTA, oligomycin (2.5 pg/ ml), antimycin (2.5 &ml) and lows M rotenone.…”
Section: Introductionmentioning
confidence: 99%
“…The kinetics of anion exchanges were studied by the 'inhibitor stop method', essentially as described previously [5,8]. Generally, mitochondria were incubated at 9°C for 1 min in 1.0 ml medium, the uptake started by adding the labelled substrate and stopped a few seconds later with an inhibitor, like phenylsuccinate or 1,2,3-benzene-tricarboxylate.…”
Section: Bathophenanthroline Sulfonate Was Obtained Frommentioning
confidence: 99%
“…In these experiments the K i of bathophenanthroline for citrate uptake is 25/aM and that for oxoglutarate uptake is 30 gdVl. Previous work [5] has shown that the dicarboxylate carrier has two separate binding sites, one specific for Pi and the other specific for the dicarboxylates. Figs.…”
Section: Figurementioning
confidence: 99%